Developing the computer-based auditory training program for adults with hearing impairment. - Tuz, Deniz; Isikhan, Selen Yilmaz; Yücel, Esra (Medical & Biological Engineering & Computing, 2021)
Although it is known that auditory training is essential for hearing-impaired individuals, patients do not willingly participate in auditory training sessions, because individual training is a time-consuming and costly process. Computer-based auditory training programs are under development for reducing the cost and time. The aim of this study is to develop a computer-based auditory training program and to evaluate the usability of the program by applying it to adults with normal hearing indifferent age groups and professions. The developed auditory training program consists of nine modules: identification, discrimination, recognition, auditory closure, comprehension, auditory sequencing, phonological awareness, auditory memory, and attention. Forty adults (age ranges of 25-34, 35-44, 45-54, and 55-65 years), nine audiologists, and one software engineer were included in this study. The computer-based auditory training program was applied to all individuals. An evaluation form was filled out by the participants to evaluate the usability of and satisfaction with the program, and the average performances of the individuals were calculated for each module. The form measures five usability subscales: ease of use, comprehensibility, design, satisfaction, and motivation. The professionals evaluated the program and found it to be quite positive in terms of design, ease of use, motivation, and comprehensibility, and positive in terms of the satisfaction subscale. The participants evaluated all factors and found them to be quite positive. There were no statistically significant differences between the gender, age, and computer use groups in terms of the average performance value of the modules (p > 0.05). However, a significant difference was found in the average performance for the auditory sequencing module considering the educational status of individuals (p = 0.019). Furthermore, it was determined that computer experience (> 5 years) and having a personal computer have a significant effect on auditory memory (p = 0.049) and identification (p = 0.027). These results show that the instructions and information used in the program are clear and understandable, the colors and texts used in the program are readable, the program is easy to use, and the individuals are not disturbed by the sounds used in the program. However, it would be valuable to apply it to individuals with hearing losses to evaluate the efficacy of the program.